(3GdfGSN hGdefShN aj GdbQBfs - (3GdHZOGOj, GHf SdGeI, CHh GdbGSe, gHI Gddg Hf SdGeI Hf fUQ Hf Ydj, (B410 (3g`s
(3ChdgG (B:s
(3bGd CHh GdbGSe gHI Gddg Hf SdGeI Hf fUQ Hf Ydj GdeaSQ GdHZOGOj QMeI Gddg Ydjg (B: (3GdMeO ddg GdPj gOGfG dOjfg hLYdfG ef Cgdg hHYO aCbd eG jfHZj def CMH Cf jJYde TjFG ef Yde gPG GdcJGH Cf dG jfXQ EdG aj Yde GdfGSN hGdefShN deG QCjJ GdeaSQjf bO SdchG WQjb gPG GdYde hde jCJhG efg hLg GdMaX s
(3BNQgG (B:s
(3ShQI GdENdGU hGdadb hGdfGS GNJda GdeaSQhf aj JfRjdgf gd gj ecjGJ Ce eOfjGJ abGd GdCcKQhf gj eOfjGJ hbGd GdVMGc hGdSOj ecjGJ hcdgf eMce djS ajgG fGSN hdG efShNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 / 72s
(3eYLe GdeDdajf (B4 / 56s
(3cTa GdXfhf (B2 / 1921s
(3ZGjI GdfgGjI (B2 / 351s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs